Mitochondria are secreted in extracellular vesicles when lysosomal function is impaired - Wenjing Liang; Shakti Sagar; Rishith Ravindran; Rita H. Najor; Justin M. Quiles; Liguo Chi; Rachel Y. Diao; Benjamin P. Woodall; Leonardo J. Leon; Erika Zumaya; Jason Duran; David M. Cauvi; et al. (Nature Communications, 2023)
Abstract Mitochondrial quality control is critical for cardiac homeostasis as these organelles are responsible for generating most of the energy needed to sustain contraction. Dysfunctional mitochondria are normally degraded via intracellular degradation pathways that converge on the lysosome. Here, we identified an alternative mechanism to eliminate mitochondria when lysosomal function is compromised. We show that lysosomal inhibition leads to increased secretion of mitochondria in large extracellular vesicles (EVs). The EVs are produced in multivesicular bodies, and their release is independent of autophagy. Deletion of the small GTPase Rab7 in cells or adult mouse heart leads to increased secretion of EVs containing ubiquitinated cargos, including intact mitochondria. The secreted EVs are captured by macrophages without activating inflammation. Hearts from aged mice or Danon disease patients have increased levels of secreted EVs containing mitochondria indicating activation of vesicular release during cardiac pathophysiology. Overall, these findings establish that mitochondria are eliminated in large EVs through the endosomal pathway when lysosomal degradation is inhibited.